Genetic instability and transitional cell carcinoma of the bladder. - Catto, J; Meuth, M; Hamdy, F (2004)
The development of cancer occurs in a stepwise fashion, with each step representing the mutation in one of several key genes. However, the mutation rate of somatic cells is too low to account for the number of mutations required for a cell to undergo carcinogenesis. Thus, the development of genetic instability is a vital early step towards carcinogenesis. We review the evidence for genetic instability, with particular reference to transitional cell carcinoma of the bladder. Both microsatellite instability and chromosomal instability are present in this tumour, and we discuss their incidence and clinical implications.